2005
DOI: 10.1007/s00216-004-2996-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the recovery of selenomethionine from selenized yeast by two-dimensional LC–ICP MS

Abstract: Determination of selenomethionine in selenized yeast by HPLC-ICP MS has been revisited with the focus on recovery of this amino acid during the proteolytic digestion and chromatography steps. Recovery of the extracted selenium from an anion-exchange column was 100% but selenomethionine quantified by the method of standard additions accounted only for 67% of the selenium injected. Analysis (by size-exclusion LC-ICP MS) of the eluate collected before and after the selenomethionine peak showed the presence of oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 23 publications
2
40
0
1
Order By: Relevance
“…The main reason for the increased Se deposition in eggs by SY is that the majority of Se in SY is selenomethionine, a Se analogue of methionine (Kelly and Power, 1995). The other organic Se components have not yet been clearly identified, but act as Se-Met precursors, although there is some recent evidence (Polatajko et al, 2005) that selenomethionine represents approximately 80% of the organic selenium in Se yeast, in some cases reaching levels of over 90% (Schrauzer, 2006). Se-Met is deposited in the egg to a greater extent than selenium selenite, and is actively absorbed and incorporated into eggs as effectively as methionine (Combs and Combs, 1986).…”
Section: Selenium In Eggsmentioning
confidence: 99%
“…The main reason for the increased Se deposition in eggs by SY is that the majority of Se in SY is selenomethionine, a Se analogue of methionine (Kelly and Power, 1995). The other organic Se components have not yet been clearly identified, but act as Se-Met precursors, although there is some recent evidence (Polatajko et al, 2005) that selenomethionine represents approximately 80% of the organic selenium in Se yeast, in some cases reaching levels of over 90% (Schrauzer, 2006). Se-Met is deposited in the egg to a greater extent than selenium selenite, and is actively absorbed and incorporated into eggs as effectively as methionine (Combs and Combs, 1986).…”
Section: Selenium In Eggsmentioning
confidence: 99%
“…This case study underlines that isotope dilution is not a panacea for accurate speciation and it demonstrates clear inefficiency of isotope dilution to obtain correct results unless analyst has ensured either complete analyte/spike equilibration or extraction. Polatajko et al also re-emphasized that many results reported for the concentration of SeMet in Seenriched yeast may be negatively biased [49].…”
Section: Isotopic Equilibration and Extraction Efficiencymentioning
confidence: 93%
“…For instance, SeMet may not be fully liberated from the protein, peptide or other cellular components with which it is associated, and it may be solubilised in forms which get lost during the derivatisation or chromatography steps or may interact non-specifically with sample components [40]. It must also be noted that Se-containing proteins are labile and prone to degradation after being extracted [41] leading to an underestimation of the Se content.…”
Section: Determination Of Total Free and Bound Selenomethioninementioning
confidence: 99%
“…To determine the variation in protein content between batches and products, label-free mass-spectrometry-based proteomic analysis, scatter correlation plots and hierarchical clustering were performed. As previously mentioned, a proteomic approach such as LC-MS/MS can circumvent potential issues with extraction, enzymatic digestion and incomplete derivatisation associated with Se speciation studies [40].…”
Section: Determination Of Inter-batch and Inter-product Protein Contementioning
confidence: 99%